2018
DOI: 10.7554/elife.32911
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ‘safe zones’ at the nuclear envelope ensure robust replication of heterochromatic chromosome regions

Abstract: Chromosome replication and transcription occur within a complex nuclear milieu whose functional subdomains are beginning to be mapped out. Here we delineate distinct domains of the fission yeast nuclear envelope (NE), focusing on regions enriched for the inner NE protein, Bqt4, or the lamin interacting domain protein, Lem2. Bqt4 is relatively mobile around the NE and acts in two capacities. First, Bqt4 tethers chromosome termini and the mat locus to the NE specifically while these regions are replicating. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 100 publications
3
53
3
Order By: Relevance
“…Recently, two studies have suggested that the localization of the mating-type region at the nuclear periphery might be part of its silencing mechanism. First, it was reported that H3K9me is considerably reduced in the mating-type region in mutants lacking the nuclear membrane protein Bqt4 (35). Second, mutants in the nuclear rim protein Amo1 were also reported to reduce H3K9me in the mat2-mat3 region, in particular outside cenH, attributed to defective maintenance (17).…”
Section: S6 and S7 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two studies have suggested that the localization of the mating-type region at the nuclear periphery might be part of its silencing mechanism. First, it was reported that H3K9me is considerably reduced in the mating-type region in mutants lacking the nuclear membrane protein Bqt4 (35). Second, mutants in the nuclear rim protein Amo1 were also reported to reduce H3K9me in the mat2-mat3 region, in particular outside cenH, attributed to defective maintenance (17).…”
Section: S6 and S7 Andmentioning
confidence: 99%
“…In the case of Amo1, reduced H3K9me was accompanied by partial delocalization from the nuclear periphery (17). In the case of Bqt4, reduced H3K9me was accompanied by partial delocalization from the nuclear periphery specifically during replication (35). Because anchoring at the nuclear periphery by the boundary elements could be part of their mechanism of action, we conducted an epistasis analysis to investigate the effects of combining mutations at IR-R with mutations in potential anchors at the nuclear envelope.…”
Section: S6 and S7 Andmentioning
confidence: 99%
“…Lem2 localizes at the INM and beneath the SPB, but biased to the SPB [128,129]. These localizations depend on Csi1 for the SPB and Bqt4 for the NE, respectively.…”
Section: Regulation Of Lem2 Localizationmentioning
confidence: 94%
“…Lem2 also interacts with chromatin regions close to the sub-telomeric heterochromatin region [124]. ChIP-seq and ChIP-chip analyses show that Lem2 binds to the telomere side of sub-telomeric heterochromatin at tel3L and tel3R, but no significant enrichment at tel1L and tel2L regions [33,124,129]. Loss of Lem2 shows de-repression of tlh1/2 genes located within the sub-telomeric region but does not affect H3K9me2 levels in this region [33].…”
Section: Lem2 On Telomeric Heterochromatinmentioning
confidence: 99%
See 1 more Smart Citation